Role And Significance Of Kisspeptin In The Female Reproductive System - F.A.Xaydarova; N.M. Baqoyeva; Y.X.Turakulov (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
The functioning of the female reproductive system depends on the proper development and regulation of the hypothalamic-pituitary-ovarian axis. It is based on the secretion of GnRH, which stimulates the secretion of luteinizing hormone (LH) and follicle-stimulating hormone (FSH). There have been many studies investigating the factors that regulate the secretion of gonadotropins. In recent years, the significance and role of kisspeptin and its receptor has aroused interest. This review will provide data from foreign studies and literature on the role of kisspeptin in the regulation of the female reproductive system.